Current problems of modern teaching methods in the distance education system - Gafarova Shaxnoza Sharifovna; Klicheva Amira Bekmurodovna (Euro Asian Journal Publishing, 2024)
In recent years, the spread of distance education has radically changed the methods of knowledge distribution and acquisition. However, along with its undoubted advantages, the transition to online education has also created a number of challenges for teachers. This article examines various challenges associated with modern teaching methods in distance education and provides insight into potential solutions to improve the effectiveness of online teaching practices
Keywords: Distance Education; Online Education; Teaching Methods; Student Engagement